Pitch properties of infant-directed speech specific to word-learning contexts: a cross-linguistic investigation of Mandarin Chinese and Dutch. Issue 1 (January 2020) - HAN, Mengru; DE JONG, Nivja H.; KAGER, René
Abstract: This study investigates the pitch properties of infant-directed speech (IDS) specific to word-learning contexts in which mothers introduce unfamiliar words to children. Using a semi-spontaneous story-book telling task, we examined (1) whether mothers made distinctions between unfamiliar and familiar words with pitch in IDS compared to adult-directed speech (ADS); (2) whether pitch properties change when mothers address children from 18 to 24 months; and (3) how Mandarin Chinese and Dutch IDS differ in their pitch properties in word-learning contexts. Results show that the mean pitch of Mandarin Chinese IDS was already ADS-like when children were 24 months, but Dutch IDS remained exaggerated in pitch at the same age. Crucially, Mandarin Chinese mothers used a higher pitch and a larger pitch range in IDS when introducing unfamiliar words, while Dutch mothers used a higher pitch specifically for familiar words. These findings contribute to the language-specificity of prosodic input in early lexical development.